2018
DOI: 10.1002/hyp.13211
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater and surface water connectivity within the recharge area of Guarani aquifer system during El Niño 2014–2016

Abstract: Recharge areas of the Guarani Aquifer System (GAS) are particularly sensitive and vulnerable to climate variability; therefore, the understanding of infiltration mechanisms for aquifer recharge and surface run‐off generation represent a relevant issue for water resources management in the southeastern portion of the Brazilian territory, particularly in the Jacaré‐Pepira River watershed. The main purpose of this study is to understand the interactions between precipitation, surface water, and groundwater using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 68 publications
2
9
0
4
Order By: Relevance
“…In the northern part of the GAS, a wide variation of isotopic δ 18 O and δ 2 H values was observed, suggesting that no evaporation processes had taken place prior to recharge (Aravena, ). Later, Batista et al (), in a minor scale study in a GAS recharge area, revealed isotopes data showing secondary evaporation processes during GAS recharge events. In the southern part, isotopic composition was slightly different, being correlated more directly to the air masses responsible for precipitation in that region.…”
Section: Evolution Of Isotope Applicationsmentioning
confidence: 97%
“…In the northern part of the GAS, a wide variation of isotopic δ 18 O and δ 2 H values was observed, suggesting that no evaporation processes had taken place prior to recharge (Aravena, ). Later, Batista et al (), in a minor scale study in a GAS recharge area, revealed isotopes data showing secondary evaporation processes during GAS recharge events. In the southern part, isotopic composition was slightly different, being correlated more directly to the air masses responsible for precipitation in that region.…”
Section: Evolution Of Isotope Applicationsmentioning
confidence: 97%
“…The distinct isotopic pulses or input functions provided by rainfall in the tropics are commonly damped or modified by different ecological and hydrogeological processes across the landscape. Connectivity between groundwater and surface water compartments have been widely studied in humid tropical watersheds (Gordon et al, 2015;Lagomasino et al, 2015;Batista et al, 2018;Oiro et al, 2018;Villegas et al, 2018;Welsh et al, 2018;Tsuchihara et al, 2019); however, large scale or regional approaches are uncommon across tropical biomes. Figure 9 shows locations of groundwater (N 1,156) and surface water (N 603) sampling efforts across Costa Rica (2016-2019).…”
Section: Groundwater and Surface Water Connectivitymentioning
confidence: 99%
“…Kirchheim, Gastmans, and Chang () reviewed how stable isotope and noble gas methods have influenced the evolution of knowledge on the Guaraní aquifer (Brazil) groundwater circulation models in the past decades. Batista et al () studied groundwater and surface water connectivity within the recharge area of the same aquifer. Their isotopic mass balance and hydrograph separation estimated variations between 70% and 80% in the groundwater contribution during the last strong ENSO event coupled with a notable correlation of d ‐excess between surface and groundwater reservoirs.…”
Section: Land Vegetation Processesmentioning
confidence: 99%